Elevated transaminases in a COVID-19 positive patient at term of gestation: a case report: Covid19 and pregnancy - Nkeih, Claudia; Sisti, Giovanni; Schiattarella, Antonio (Acta Biomedica Atenei Parmensis, 2020)
Background: The coronavirus disease 2019 (COVID-19) pandemic is caused by the severe acute respiratory syndrome 2 virus (SARS-CoV-2) and it is spreading worldwide with an alarming high transmission rate. SARS-CoV-2 usually attacks the lungs causing a wide range of symptoms ranging from mild dyspnea to severe shortness of breath requiring intubation. Elevation of liver transaminases in the patients’ sera has been described in up to 53% of the COVID-19 positive patients. The underlying pathogenic mechanisms of the virus on the liver cells are unclear and only few hypotheses are currently available. Data on COVID-19 in pregnant women are lacking and the management of COVID-19 pregnant women is challenging. An elevation of the transaminases during pregnancies infected by SARS-CoV-2 has never been described before. Methods: Here we presented the case of a 29 years-old patient at 38 weeks of gestation COVID-19 positive with elevated transaminases. Results: The patient showed a progressive decrease of transaminases after the delivery of the fetus. We provided details about the daily transaminases trend, the therapy used and the maternal/neonatal outcomes. Conclusions: We speculate that in our case the delivery of the fetus contributed to the normalization of the liver enzymes. In patients affected by COVID-19, at term of gestation, with elevated transaminases, delivery of the fetus is an appealing option. If confirmed by larger studies, our proposed management might be incorporated in the obstetrical management guidelines for COVID-19 positive patients.